2021
DOI: 10.1177/21925682211039498
|View full text |Cite
|
Sign up to set email alerts
|

Who Needs Surgical Stabilization for Pyogenic Spondylodiscitis? Retrospective Analysis of Non-Surgically Treated Patients

Abstract: Study Design: Retrospective case series analysis. Objective: To identify relevant clinical and radiographic markers for patients presenting with infectious spondylo-discitis associated with spinal instability directly related to the infectious process. Methods: We evaluated patients presenting with de-novo intervertebral discitis or vertebral osteomyelitis /discitis (VOD) who initiated non-surgical treatment. Patients who failed conservative treatment and required stabilization surgery within 90 days were defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…After admission or referral to the emergency unit, the assessment of patient status is of the upmost importance to determine proper diagnostic steps and the following treatment. Scores for sepsis have long been used to improve a patient's assessment and treatment outcomes as an essential tool in modern clinical practice [29]. We therefore highlight the need for fitting tools to be implemented to further improve the level of care when S is diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After admission or referral to the emergency unit, the assessment of patient status is of the upmost importance to determine proper diagnostic steps and the following treatment. Scores for sepsis have long been used to improve a patient's assessment and treatment outcomes as an essential tool in modern clinical practice [29]. We therefore highlight the need for fitting tools to be implemented to further improve the level of care when S is diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, 100 patients (33%) showed signs of sepsis at administration, and 76 (25%) patients developed such complication during their hospital stay. The Sepsis-3 criteria introduced in 2016 describe sepsis as a life-threatening immune response to infection [29]. Considering existing sepsis guidelines, any kind of organ dysfunction in patients with S must be considered a red flag [35].…”
Section: Discussionmentioning
confidence: 99%
“…8,21 The preservation of spinal stability in an acceptable alignment is one of the core objectives of spinal infection treatment; however, variables surrounding spinal instability in DNSI have been poorly defined. 6,10,12,13,22 In trying to address this deficiency, we sought to draw on the previously accepted general principles applied in SINS 23 and by Panjabi, 12 thereby defining spinal instability in DNSI as a loss of spinal integrity from an infectious process associated with or without neural element impingement, symptomatic or progressive deformity, and pain associated with mechanical loading or an inability to ambulate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on currently limited evidence, several studies have shown a higher failure rate of medical treatment for DNSI patients with diabetes mellitus. 10,30,35,36 The impact of a history of IVDA on treatment outcomes appears to be more complex. Previous studies have demonstrated a higher failure rate among IVDA patients treated medically along with an increased probability of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation